Immunogenicity of Bone Graft Using Xenograft Freeze-Dried Cortical Bovine, Allograft Freeze-Dried Cortical New Zealand White Rabbit, Xenograft Hydroxyapatite Bovine, And Xenograft Demineralized Bone Matrix Bovine In Bone Defect Of Femoral Diaphysis White Rabbit Experimental Study In Vivo - Ferdiansyah, Ferdiansyah; Utomo, Dwikora Novembri; Suroto, Heri (KnE Life Sciences, 2017)
Bone defect remains a big challenge for orthopedic surgeon. Bone grafting nowadays become the second common transplantation after blood transfusion. Autogenous bone graft is the gold standard in treatment of bone defect, but it’s source limitation and donor site morbidity makes some surgeon were looking for allograft or xenograft. There are some issues with allo- and xenograft about difficulty in corporation and rejection reaction. This study explores the immunogenicity of allograft and xenograft. Keyword : freeze-dried xenograft, freeze-dried allograft, hydroxyapatite xenograft, demineralized bone matrix xenograft.